213Traditional Japanese Diet Score and healthy life expectancy - a longitudinal global study. (2nd September 2021) - Imai, Tomoko; Sezaki, Ayako; Miyamoto, Keiko; Abe, Chisato; Kawase, Fumiya; Shirai, Yoshiro; Inden, Ayaka; Kato, Takumi; Sanada, Masako; Shimokata, Hiroshi
Abstract: Background: Traditional Japanese diets are considered to be health and longevity. We created a Traditional Japanese Diet Score (TJDS) and investigated the relationship between the TJDS and healthy life expectancy (HALE) longitudinally using global database. Methods: Average food (g/day/capita) and energy supply (kcal/day/capita) by countries were identified by the Food and Agriculture Organization of the United Nations Statistics Division database. The sum of characterizing traditional Japanese foods supply (beneficial food components in Japanese diet; rice, fish, soybeans, vegetables, eggs, seaweeds, food components not use so much in Japanese diet; wheat, milk, and red meat) were divided as tertile (beneficial food components;-1, 0, 1, not use so much food components; 1, 0, -1). HALE values by country were derived from the Global Burden of Disease 2017 database. The longitudinal effects of TJDS on the rate of change in HALE from 1990 to 2013 were evaluated using a generalized mixed-effect model (GLMM), which takes into account the dependence of repeated observations within countries. The interaction between TJDS and survey year was applied to access the effects on HALE. This study covered 137 countries with populations of 1 million or greater. Results: Longitudinal analysis controlled for covariates showed that smooth term of the interaction between TJDS and survey year was significant (p < 0.001). The TJDS was negative associated with HALE in 1990, and in 1991, but positive associated after 2002. Conclusions: The relationship between the TJDS as a healthy eating style and HALE is getting stronger since the 21st century. Key messages: Well-balanced eating habits of traditional Japanese diets is supports healthy life expectancy.